The in vivo electrical parameters of toad skin - Eduardo, José [UNESP]; Silveira, N [UNESP]; Cirne, Bario R [UNESP] (Elsevier, 1983)
1. 1. Open-circuit voltage (PD) and short-circuit current (SCC) across toad skin were studied in in vivo conditions. An improved technique for fastening a lucite chamber on the abdominal region of the animal was developed. 2. 2. Saline bridges (230 mM Nacl in 4% agar solution) were placed subcutaneously to make the connections between the extracellular fluid and the half-cells. 3. 3. A clear relationship was observed between the electrical parameters and sodium transport by the skin, since PD and SCC were related to the sodium concentration of the bathing solution, and abolished by the presence of amiloride-a specific sodium transport inhibitor in epithelia. 4. 4. The initial control values of SCC in vivo were higher than those in vitro, which was attributed to hormonal stimulation. However, these high initial control values of SCC in vivo fell with time, reaching steady levels after a 2 hr period. 5. 5. Vasopressin failed to increase SCC in vivo when the external sodium concentration was 115 mM, being effective only when the sodium concentration was low (5 mM). 6. 6. On the other hand, in isolated preparations vasopressin significantly promoted an increase in both PD and SCC. © 1983.
Keywords: sodium; active transport; animal; comparative study; electrophysiology; functions of the skin and its appendages; metabolism; physiology; technique; toad; Animal; Biological Transport, Active; Bufo marinus; Comparative Study; Electrophysiology; Methods; Skin Physiology; Sodium